Penerapan Model Guided Inquiry Learning untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi Siswa SMA - Asri Nur Azizah; Baskoro Adi Prayitno; Nurmiyati Nurmiyati (Universitas Sebelas Maret, 2019)
This research aimed to improve the high-order thinking ability in the 11th MIA 3 graders of SMA Negeri 1 Teras in the school year of 2015/2016 by applying Guided Inquiry Learning model. This study was a Classroom Action Research using Kemmis and Mc.Taggart’s spiral model. The research was conducted in two cycle. Each of cycle consisted of four stages: planning, acting, observing, and reflecting. The objective of research was the 11th MIA 3 graders of SMA Negeri 1 Teras in the school year of 2015/2016, consisting of 34 students. The data of research was obtained through observation, interview, documentation and high-order thinking ability test. Data validation was carried out using triangulation technique. Data analysis was conducted using descriptive qualitative analysis technique. The target of research was an increase by ≥25% in every aspect of high-order thinking ability, ie C4 (analyzing) aspect increased by 25% from 45. 53% to 70.53%, C5 (evaluating) aspect increased by 25% from 47.72% to 72.72%, and C6 (creating) aspect increased by 25% from 48.24% to 73.24%. The result of research showed that the application of Guided Inquiry learning could improve the high-order thinking ability of the students including C4 (analyzing), C5 (evaluating), and C6 (creating) aspects corresponding to the target of research, ≥25%. The percentage gain of C4 was 45.53% in pre-cycle, 82.84% in cycle I, and 87.62% in cycle II. The percentage gain of C5 was 47.72% in pre-cycle, 73.54% in cycle I, and 83.82% in cycle II. The percentage gain of C6 was 48.24% in pre-cycle, 73.53% in cycle I, and 75.12% in cycle II. C4 (analyzing) aspect increased by 42.09% from .53% to 87.62%, C5 (evaluating) aspect increased by 36.1% from 47.72% to 83.82%, and C6 (creating) aspect increased by 26.88% from 48.24% to 75.12%. Considering the result of research, it could be concluded that the application of Guided Inquiry Learning could improve the high-order thinking ability in the 11th MIA 3 graders of SMA Negeri 1 Teras in the school year of 2015/2016.